A Survey of Fellowship-Trained Upper Extremity Surgeons on Treatment of Lateral Epicondylitis. (September 2019) - Niedermeier, Steven R.; Crouser, Nisha; Speeckaert, Amy; Goyal, Kanu S.
Background: The aim of the study is to investigate current management strategies for lateral epicondylitis by fellowship-trained upper extremity surgeons.Methods: A 17-question survey of treatment approaches and outcomes related to lateral epicondylitis was sent to 3354 surgeons using the American Society for Surgery of the Hand and American Shoulder and Elbow Surgeons member databases.Results: Six hundred twelve upper extremity surgeons completed the survey. The 6 most frequently prescribed nonoperative treatments for lateral epicondylitis were home exercise program/stretching (81%), nonsteroidal anti-inflammatory drugs (75%), steroid injection (71%), counterforce bracing (68%), formal physical therapy (65%), and wrist brace (47%). Less commonly performed nonoperative treatment measures included platelet-rich plasma injection (16%), Tenex procedure (6%), and iontophoresis (2%).Conclusions: There is a lack of consensus in the literature for the management of lateral epicondylitis, which is reflected by individual variation in clinical treatment among the experts. Future prospective randomized control studies are needed to establish evidence-based practice standards for this common diagnosis.